2017
DOI: 10.1111/vde.12512
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of the IL‐33 receptor suppression of tumourigenicity 2 and its effects on canine Type 2 T helper cells: a preliminary study

Abstract: These results indicate that canine Th2 cells activated by IL-33 enhance Th2-mediated inflammation through the production of IL-5 and IL-13.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…A previous study reported an increase in the expression of IL‐33 in keratinocytes of the lesional skin of cAD 2 . IL‐33 also was shown to enhance IL‐5 and IL‐13 mRNA transcriptions in canine Th2 cells 3 . These findings suggest that IL‐33 produced by keratinocytes is involved in the pathogenesis of cAD.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…A previous study reported an increase in the expression of IL‐33 in keratinocytes of the lesional skin of cAD 2 . IL‐33 also was shown to enhance IL‐5 and IL‐13 mRNA transcriptions in canine Th2 cells 3 . These findings suggest that IL‐33 produced by keratinocytes is involved in the pathogenesis of cAD.…”
Section: Introductionmentioning
confidence: 54%
“…2 IL-33 also was shown to enhance IL-5 and IL-13 mRNA transcriptions in canine Th2 cells. 3 These findings suggest that IL-33 produced by keratinocytes is involved in the pathogenesis of cAD. However, it remains unclear what factors have the potential to induce or increase IL-33 mRNA expression in canine keratinocytes.…”
Section: Introductionmentioning
confidence: 86%
“…67 Suppression of tumorigenicity 2 (ST2), a receptor for IL-33, was expressed on canine Th2 cells, and stimulation of cells with IL-33 led to the expression of type 2 cytokines. 68 Furthermore, significant upregulation of IL-33 was found in chronic lesional skin of canine AD. 69 Although GATA3 + ILC2-like cells were not increased in the peripheral blood of AD dogs, 59 further work should evaluate ST2 + or TSLPR + ILC2 in atopic skin of dogs.…”
Section: Innate Immunity In Admentioning
confidence: 96%
“…The expression of TSLP was enhanced in an in vitro culture of canine keratinocytes after exposure to toll‐like receptor 1 or 2 ligand 67 . Suppression of tumorigenicity 2 (ST2), a receptor for IL‐33, was expressed on canine Th2 cells, and stimulation of cells with IL‐33 led to the expression of type 2 cytokines 68 . Furthermore, significant upregulation of IL‐33 was found in chronic lesional skin of canine AD 69 .…”
Section: Innate Immunity In Admentioning
confidence: 99%
“…In dogs, one study reported that IL‐33 enhanced the transcription of il‐5 and il‐13 in Th2 cells . In the present study, we investigated the transcription and expression of IL‐33 in chronic lesional skin of cAD in order to demonstrate a relationship with immunopathogenesis.…”
Section: Introductionmentioning
confidence: 99%